1989
DOI: 10.1128/mcb.9.4.1445
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of PF4varl, a human gene variant of platelet factor 4.

Abstract: A synthetic DNA probe designed to detect coding sequences for platelet factor 4 and connective tissueactivating peptide III (two human platelet a-granule proteins) was used to identify several similar sequences in total human DNA. Sequence analysis of a corresponding 3,201-base-pair EcoRI fragment isolated from a human genomic library demonstrated the existence of a variait of platelet factor 4, designated PF4varl. The gene for PF4varl consisted of three exons and two introns. Exon 1 coded for a 34-amino-acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…8 The critical role of CXCL4 in several pathophysiologic conditions is further underlined by the existence in human beings of a highly homologous gene encoding a variant of CXCL4, named as CXCL4L1. [18][19][20] CXCL4L1, compared with For personal use only. on May 12, 2018. by guest www.bloodjournal.org From CXCL4, exhibits significantly reduced heparin-binding properties and thus a lower sequestration by glycosaminoglycans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 The critical role of CXCL4 in several pathophysiologic conditions is further underlined by the existence in human beings of a highly homologous gene encoding a variant of CXCL4, named as CXCL4L1. [18][19][20] CXCL4L1, compared with For personal use only. on May 12, 2018. by guest www.bloodjournal.org From CXCL4, exhibits significantly reduced heparin-binding properties and thus a lower sequestration by glycosaminoglycans.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies hypothesized that this may imply a difference in the cell type in which CXCL4L1 is expressed or a difference in its mode of secretion. 19 However, this hypothesis has not yet been verified. The online version of this article contains a data supplement.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Other studies have reported that the inhibitory effect of CXCL4 is mediated through complex formation with bFGF or CXCL8 (53,55). Finally, CXCL4 also exists as a non-allelic gene variant, CXCL4L1, which differs from CXCL4 in its signalling region, subcellular localization, and regulation of secretion (56)(57)(58). CXCL4L1 has been found to be a more potent inhibitor of angiogenesis both in in-vitro and in in-vivo models of angiogenesis (59), but the mechanism by which this variant mediates these effects is yet to be defined.…”
Section: Chemokine-mediated Inhibition Of Angiogenesis Via Undefined mentioning
confidence: 99%
“…The proposed receptor for CXCL4/PF-4, named CXCR3-B (14), might not mediate all its effects. The variant of CXCL4/PF-4, encoded by a second nonallelic gene and differing in only three amino acids, is named CXCL4L1/PF-4var (15,16) and was isolated from thrombin-stimulated platelets (17). In a previous study, we showed that CXCL4L1/PF4var is also produced by osteosarcoma cells (18).…”
Section: Introductionmentioning
confidence: 99%